Hepatitis B virus infection profile in hemodialysis patients in Central Brazil: prevalence, risk factors, and genotypes - Ferreira, Renata C. (2006)
Universidade Federal de Goiás. Instituto de Patologia Tropical e Saúde Pública. Goiânia, GO, Brasil.